The new rules of marketing & PR how to use content marketing, AI, social media, podcasting, video, and newsjacking to reach buyers directly - Scott, David Meerman (John Wiley & Sons, Inc., 2024)
"The rapid growth of generative artificial intelligence tools from AI giants like OpenAI and Google, plus a host of smaller startups, is the most significant development in modern marketing and PR since the first edition of the book was published back in 2007. Marketers and PR professionals who don't embrace these new technologies will quickly fall behind, putting them at a substantial competitive disadvantage compared to those who use these technologies skillfully. Therefore, the 9th edition is the most important update to the book yet. David Meerman Scott serves as an advisor to five AI companies and has used AI himself for years. In this new edition, he breaks through the hype to provide practical information and stories of success so readers can not only understand AI but also deploy AI tools in any size business. At the same time, while machines can certainly aid marketing in unprecedented ways, the 9th edition also shows why we need writers and designers and filmmakers and other creative people now more than ever. We learn insights about life from creatives in a way that AI never can--because AI can only build on what has come before. It's important to remember that we need human-centric communications to show how organizations are making people's lives better. In a world of AI, good communications, practiced by good humans, matters deeply."--
Includes index. - Description based on online resource; title from digital title page (viewed on September 17, 2024)
Keywords: Internet marketing; Internet in public relations; Marketing sur Internet; Internet dans les relations publiques